An Information System Study on the Supply Section of the Philippine Heart Center - Aguirre, Leilani; Alejandrino, Rosamaria; Dee, Geraldine; Pe, Jane; Sucalit, Sheila (College of Engineering, 1989)
In the 14 years that the Philippine Heart Center has been operating, much has already been done to improve the Material Management system of the hospital starting out as the Property and Procurement Department, it has been recently re-organized to become a joint effort of two departments, Purchasing and Property and Supply Department. Nevertheless, improvements can still be done especially on the Supply Section. Therefore, it has been chosen as an ideal system to study. However, the group cautions that this exercise, being purely academic, does not promise to be excellent.